EFFECTS OF FINANCIAL SECTOR LIBERALIZATION ON BANK PERFORMANCE IN NIGERIA: 1971-2011 - ADESEGUN, OWOLABI (British Journal of Marketing Studies, 2014)
The study critically assessed the extent to which financial sector liberalization has affected bank performance in Nigeria. Panel data model was employed for data spanning a period of thirty four years (i.e. 1971-2011). Earnings per share (EPS), Returns on capital employed (ROCE) and Returns on equity (ROE) were used as proxies for bank performance (i.e the dependent variables) while interest rate, real financial savings and exchange rates were used as the proxies for financial sector liberalization (i.e. the independent variables). A number of diagnostic tests were also conducted on the residuals to evaluate the models; these include the Breuch-Godfrey serial correlation Lagrange Multiplier (LM) test, the Ramsey REST test of specification error (i.e. to test for omitted variables, incorrect functional form, correlation between exogenous variables and error term) and the Cumulative Sum (CUSUM ) tests of parametric stability, the LM test of serial correlation showed that there was an absence of first order serial correlation in the residuals and cumulative sum tests also showed that observations are more stable during Pre-SAP period than the post-SAP era. The result obtained showed that though the effect of financial sector liberalization on bank performance in Nigeria for the period of study has been significant, especially as measured by the proxies of Earnings per Share and Return on Equity, it has not been significant enough to transform the nations' economy to the desired level. Hence, the study suggests among other things that a precondition for the efficiency of a liberalized financial sector is a stable macroeconomic environment and it is essential to ensure that government fiscal policy is assigned to complement monetary policies not to work against monetary and fiscal policies and help restore domestic and international confidence in the Nigeria banking system.